HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PENANGANAN DISMENORE PADA SISWA PEREMPUAN SMP MA'ARIF 01 SEPUTIH RAMAN - Riani Riani; Hikmah Ifayanti; Yona Desni Sagita; Rini Palupi (MOTORIK Jurnal Ilmu Kesehatan, 2024)
Dysmenorrhea is a painful phenomenon experienced during menstruation, often accompanied by cramps and focused on the lower abdomen that spreads to the lower back and thighs. This study aims to determine the relationship between knowledge and attitudes towards treating dysmenorrhoea among female students at SMP Ma'arif 01 Seputih Raman. The research uses a quantitative approach with a cross-sectional design. Total sampling was carried out on 83 female students at SMP Ma'arif 01 Seputih Raman. Bivariate analysis uses the Chi Square Test. The results of univariate analysis showed that 22 female students (68.8%) treated dysmenorrhoea poorly, while only 10 female students (31.3%) managed it well. Bivariate analysis showed that there was no significant relationship between female students' knowledge of dysmenorrhea treatment (p value 0.617 > 0.05). However, there is a significant relationship between female students' attitudes and the treatment of dysmenorrhea (p value 0.048 < 0.05). So there is a need to improve the attitudes of female students regarding the treatment of dysmenorrhea